2015
DOI: 10.4049/jimmunol.1501273
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Simian Immunodeficiency Virus Infection Causes Ultimate Depletion of Follicular Th Cells in AIDS

Abstract: Follicular CD4+ T helper (Tfh) cells are critical for the generation of humoral immune responses to pathogenic infections, providing help for B cell development, survival, and affinity maturation of antibodies. Although CD4+ Tfh cells are reported to accumulate in HIV or SIV infection, here we found that germinal center (GC) Tfh cells, defined here as CXCR5+PD-1HIGHCD4+ T cells, did not consistently accumulate in chronically SIV-infected rhesus macaques compared with those infected with less pathogenic SHIV, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 37 publications
3
46
2
Order By: Relevance
“…2D and E). Interestingly, many GC Tfh cells were also able to produce SIV RNA, suggesting that at least the infected GC Tfh cells are activated, which is supported by their higher levels of HLA-DR and Ki-67 expression (17). These findings suggest that GC Tfh cells are major sources of both latent and productive SIV infection in SIVinfected macaques, consistent with previous studies of HIV-infected humans (23).…”
Section: Int Cd4supporting
confidence: 89%
See 1 more Smart Citation
“…2D and E). Interestingly, many GC Tfh cells were also able to produce SIV RNA, suggesting that at least the infected GC Tfh cells are activated, which is supported by their higher levels of HLA-DR and Ki-67 expression (17). These findings suggest that GC Tfh cells are major sources of both latent and productive SIV infection in SIVinfected macaques, consistent with previous studies of HIV-infected humans (23).…”
Section: Int Cd4supporting
confidence: 89%
“…Recent reports suggest that Tfh cells accumulate in simian immunodeficiency virus (SIV)/human immunodeficiency virus (HIV) infections (10,(12)(13)(14), and LN-derived CXCR5 ϩ Tfh cells serve as reservoirs for productive viral infection and replication (10,15,16). We recently reported that CXCR5 ϩ PD-1 HGIH CD4 ϩ T cells in LNs are transiently reduced in acute infection (day 14 after SIV infection) and accumulate in chronic infection yet are ultimately depleted in animals with AIDS (17). However, the mechanisms behind their infection and this accumulation remain unclear.…”
Section: F Ollicular T Helper (Tfh) Cells Are a Class Of Helper Cd4mentioning
confidence: 99%
“…Despite the susceptibility of Tfh cells to infection with SIV/HIV, the frequency of GC Tfh cells begins to increase within a few months of infection188 and elevated Tfh cell numbers are routinely observed in LNs during chronic SIV and HIV infections,168, 173, 189, 190, 191 although Tfh cells are eventually depleted as progression to acquired immunodeficiency syndrome (AIDS) occurs 192. The expansion in Tfh cells is associated with an increase in GC B cells and plasma cells and elevated IgG production, suggesting that Tfh cells contribute to the dysregulation of B cells and antibody production that occurs during HIV‐1 infection 191.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…Circulating T FH are decreased in untreated chronically-HIV infected individuals [25], suggesting that the GC offers a unique environment allowing for T FH expansion. It should be noted that in advanced infection, T FH expansions and GC morphology are lost and this is associated with the onset of SAIDS in rhesus macaques [26] and AIDS in humans [27]. …”
Section: Role Of Tfh In Hiv Replication In Untreated Diseasementioning
confidence: 99%